2021
DOI: 10.1016/j.jcis.2020.07.107
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic core–shell silica nanoparticles using a dual-functional peptide

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Inorganic NPs, such as silica NPs, metal NPs (e.g., Au), metal oxide NPs (e.g., iron oxide), and quantum dots (e.g., CdS and CdSe) generally exhibit superior mechanical and chemical stability, lower polydispersity, richer surface chemistry and surface morphology, and larger surface area (for porous NPs) compared to organic NPs. [ 161–163 ] Moreover, many inorganic NPs also possess special optical, photothermal, and magnetic properties that can be leveraged for theranostics, thermotherapy and magnetically induced tumor targeting, etc. These unique features render inorganic NPs promising candidates for drug delivery applications, thus they have been widely fabricated via various approaches in the past decades.…”
Section: Microfluidic Synthesis Of Inorganic Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic NPs, such as silica NPs, metal NPs (e.g., Au), metal oxide NPs (e.g., iron oxide), and quantum dots (e.g., CdS and CdSe) generally exhibit superior mechanical and chemical stability, lower polydispersity, richer surface chemistry and surface morphology, and larger surface area (for porous NPs) compared to organic NPs. [ 161–163 ] Moreover, many inorganic NPs also possess special optical, photothermal, and magnetic properties that can be leveraged for theranostics, thermotherapy and magnetically induced tumor targeting, etc. These unique features render inorganic NPs promising candidates for drug delivery applications, thus they have been widely fabricated via various approaches in the past decades.…”
Section: Microfluidic Synthesis Of Inorganic Npsmentioning
confidence: 99%
“…to organic NPs [161][162][163]. Moreover, many inorganic NPs also possess special optical, photothermal, and magnetic properties that can be leveraged for theranostics, thermotherapy and magnetically induced tumor targeting, etc.…”
mentioning
confidence: 99%
“…For example, highly ordered biosilica with precise control over obtained inorganic material nanostructures was fabricated by the biomimetic synthesis using biomolecules and tetraethyl orthosilicate (TEOS) or tetramethyl orthosilicate (TMOS) as the templates and the precursor, respectively. 9 In addition, TiO 2 and other composite materials were synthesized by biomimetic mineralization using peptides as templates. 14 The CuS framework with porosity was fabricated via hydrothermal method using chitosan as a template, and the formation mechanism of the porous-structured CuS has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, different kinds of natural and synthetic macromolecule gels, supermolecule hydrogels, and inorganic gels, are suitable for growing crystals within by the bio-inspired mineralization process. A range of natural gels based on agar, 4,5 gelatin 6,7 , chitosan, 8 peptide, 9,10 β-CD, 11 and collagenous matrices 12 and other substrates 13 have been used as the gel substrate for the mineralization. For example, highly ordered biosilica with precise control over obtained inorganic material nanostructures was fabricated by the biomimetic synthesis using biomolecules and tetraethyl orthosilicate (TEOS) or tetramethyl orthosilicate (TMOS) as the templates and the precursor, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Core-shell nanomaterials comprising an inner core and an outer shell have attracted considerable attention due to their properties derived from both the core and the shell materials [ 1 , 2 , 3 , 4 , 5 ]. It has been reported that the surface reactivity [ 6 , 7 , 8 , 9 ], thermal stability [ 10 , 11 ], colloidal stability [ 12 , 13 ], dispersibility [ 14 , 15 ], absorption [ 16 , 17 , 18 ], chemical configuration transition [ 19 , 20 ], and releasing properties [ 21 , 22 ] of core-shell nanomaterials mostly depend on the chemical and physical properties of the shell material. Various encapsulation methods have been extensively studied to prepare core-shell hybrid nanomaterials with excellent functionalities [ 2 ].…”
Section: Introductionmentioning
confidence: 99%